2018
DOI: 10.1177/0886260517744846
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Victimization and Peer Harassment Involvement in a Technological World

Abstract: This article explores the ways poly-victimized youth (those experiencing multiple different types of victimization over the course of 1 year) use technology to interact with peers. Particular attention is given to the peer harassment victimization and perpetration experiences of poly-victimized youth compared with less victimized and non-victimized youth-both overall and through technology. Data were collected as part of the Technology Harassment Victimization (THV) study; a national survey of 791 youth, ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…The results of this study first showed that college-age students who were victimized by different forms of victimization (emotional abuse from parents, exposure to interparental violence, sexual touching, sexual assault, and parental neglect), taken separately, were more likely to be victimized of cyberbullying. These results corroborate other studies that have shown positive significant association between various forms of prior victimization and cyberbullying (Chen et al, 2018;Hamby et al, 2018a;Mitchell, Segura, Jones, & Turner, 2018). Although none of the identified studies have been conducted among college-age students, they have shown that young people who have experienced different forms of abuse or interpersonal violence during childhood (Hébert et al, 2016;Kircaburun, Demetrovics, Király, & Griffiths, 2018) are more likely to be cybervictimized later.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study first showed that college-age students who were victimized by different forms of victimization (emotional abuse from parents, exposure to interparental violence, sexual touching, sexual assault, and parental neglect), taken separately, were more likely to be victimized of cyberbullying. These results corroborate other studies that have shown positive significant association between various forms of prior victimization and cyberbullying (Chen et al, 2018;Hamby et al, 2018a;Mitchell, Segura, Jones, & Turner, 2018). Although none of the identified studies have been conducted among college-age students, they have shown that young people who have experienced different forms of abuse or interpersonal violence during childhood (Hébert et al, 2016;Kircaburun, Demetrovics, Király, & Griffiths, 2018) are more likely to be cybervictimized later.…”
Section: Discussionsupporting
confidence: 89%
“…These results confirm the bullying overlap [ 33 , 39 ] and demonstrate a high rate of overlap between online bullying and offline bullying. Previous research has found that adolescents who were victimized through various forms of traditional bullying exhibited more risky behavior linked with the use of technology [ 52 ]. In primary school students, the same trend is observable in relation to cyberbullying, confirming the overlap of victimization in physical and online settings in the final years of primary education [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for numerous women, nonphysical and physical assaults “seep into one another” (Ptacek, 2016, p. 128). Consider that DeKeseredy et al’s (2019) campus climate survey found that many female students experienced polyvictimization , which means having been targeted by multiple victimizations of different kinds of behaviors located on the continuum of sexual violence, not just multiple experiences of the same type of abuse (Mitchell et al, 2018).…”
Section: Moving Feminist Sociological Analyses Forwardmentioning
confidence: 99%